Bifidobacterium pseudonumeratum W112 alleviated depressive and liver injury symptoms induced by chronic unpredictable mild stress via gut-liver-brain axis - Zhao, Jingqi; Yuan, Jiahu; Zhang, Yihua; Deng, Langni; Pan, Yajing; Bai, Xiaojia; Jia, Longgang; Wang, Yanping; Geng, Weitao (Frontiers in Nutrition, 2024)
Several studies indicated that depression is associated with liver injury. The role of probiotics in alleviating depression is focused on improving the abnormalities of the central nervous system through the gut-brain axis, while the effect on liver injury is still unclear. The aim of this study was to elucidate the potential link between the antidepressant effect of a potential probiotic strain Bifidobacterium pseudocatenulatum W112 and its effect on alleviating liver injury. The 4-week-old Kunming mice were exposed to chronic stress for 4 weeks to establish a depression model. The depression-like behavior and related biomakers in chronic unpredictable mild stress (CUMS) mice were altered by supplemented with W112 for 2 weeks. Meanwhile, the modulation effect of W112 the gut microbiota in CUMS mice also result in an increase in the abundance of beneficial bacteria and a decrease in the abundance of harmful bacteria. Significantly, liver injury was observed in CUMS model mice. W112 improved liver injury by reducing AST/ALT in serum. Quantitative PCR results indicated that the mechanism of action of W112 in ameliorating liver injury was that the altered gut microbiota affected hepatic phospholipid metabolism and bile acid metabolism. In short, W112 could significantly improve the depressive and liver injury symptoms caused by CUMS. The gut-liver-brain axis is a potential connecting pathway between the antidepressant effects of W112 and its alleviation of liver injury.-This study elucidates that the gut liver brain axis is a potential connecting pathway between the antidepressant effect of W112 and its reduction of liver injury; -Bifidobacterium pseudocatenulatum W112 isolated from healthy infant feces can alleviate depression caused by CUMS by optimizing the composition of gut microbiota; -W112 can promote the normalization of neuroendocrine activity by regulating the content of relevant biomarkers in CUMS mice, which indicateed that W112 has an antidepressant function; -W112 could alleviate CUMS induced liver injury by regulting phospholipid metabolism and bile acid metabolism.